The Marvels Found in the Great Cities and in the Seas and on the Islands A Representative of 'Aǧā'ib Literature in Syriac - Minov, Sergey (Cambridge Semitic Languages and Cultures Series, 2021)
"This volume presents the original text, accompanied by an English translation and commentary, of a hitherto unpublished Syriac composition, entitled the Marvels Found in the Great Cities and in the Seas and on the Islands. Produced by an unknown East Syrian Christian author during the late medieval or early modern period, this work offers a loosely organized catalogue of marvellous events, phenomena, and objects, natural as well as human-made, found throughout the world. The Marvels is a unique composition in that it bears witness to the creative adoption by Syriac Christians of the paradoxographical literary mode of 'aǧā'ib that enjoyed great popularity among their Arabic- and Persian-speaking Muslim neighbours. In this composition, the East Syrian author blends together a number of different paradoxographical traditions: some inherited from the earlier Christian works in Syriac, such as the Alexander Romance, some borrowed directly or indirectly from Muslim geographical and other works, and some, apparently, circulating as a part of local oral lore. Combining entertainment and didacticism, he provides his audience with a fascinating panorama of imaginary geography, which at the same time has unmistakable Christian features. This edition makes a fascinating Syriac work available to a wider audience, and provides detailed insights into the rich assortment of traditions creatively woven together by its author. Thanks to the combination of the original text, English translation and commentary, it will be of interest to scholars and readers alike."